Analisis Pengaruh Modal dan Biaya Produksi Terhadap Pendapatan UMKM di Kota Gorontalo - Valentina Monoarfa; Safira Zatalia Putri Hikmah; Sri Ananda Dehimel; Syawa Oktarina Abdullah; Hadija Laima (Masyarakat Ekonomi Syariah Bogor, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the local economy, including in Gorontalo City. This study aims to analyze the effect of capital and production costs on MSME income in Gorontalo City. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 50 MSME actors. Data were analyzed using multiple linear regression. The results of the study indicate that capital and production costs have a positive and significant effect on MSME income. Capital contributes 50% to income, while production costs contribute 30%. Simultaneously, capital and production costs affect MSME income by 80%, while 20% is influenced by other factors outside this study. The implications of this study show the importance of capital management and production cost efficiency in increasing MSME income in Gorontalo City.